INOVASI BISNIS WARUNG RAJAA BASSOO DENGAN MENGGUNAKAN METODE TEN TYPES OF INNOVATION - Ramadhan, Ahmad Ferdiansyah; Rahmi, Vembri Aulia (JURNAL ILMIAH EDUNOMIKA, 2024)
The culinary business is a large market with a large population. Rajaa Bassoo has proven capable of being competitive and innovative in developing its business. This research aims to determine the innovations and tactics that have been implemented by Rajaa Bassoo and its competitors. Providing recommendations for Rajaa Bassoo's innovations and new tactics so that the business can be sustainable. This research used descriptive qualitative methods at Rajaa Bassoo on Jl Dr Wahyudin Sudiro Husodo Gang Raya 24 No 15, Randuagung Village, Kebomas District, Gresik Regency. Data was taken from one business owner, one supplier and three competitors, namely Bakso Ikip and Bakso Giman from the city of Gresik. The research results show that the business innovations that have been used by Rajaa Bassoo and its competitors, namely Bakso Giman competitors, use Premium tactics, Engaging Functionality, Complements, Process Standardization, Loyalty Programs. For Bakso Ikip competitors Disagreegate, Alliances, Process Standardization, Complements, Try Before You Buy. In new innovations that are appropriate for Rajaa Bassoo, they use Premium, Superior Product, Styling, Organizational Design, Experience Center, Values Alignment, Certification, Community And Belonging tactics. The results of other research also found a new canvas model business that was suitable for Rajaa Bassoo to run.